Perancangan Aplikasi Booking Berbasis Website Pada MUA Asri Wedding - Gita Silviana Dewi; Sunardi Sunardi; Hamdan Hamdan (BETRIK, 2025)
The rapid development of information technology has driven digital transformation across various sectors, including the beauty service industry such as Makeup Artist (MUA). Asri Wedding MUA still relies on manual booking through social media, which often leads to issues such as scheduling errors, delayed confirmations, and lack of transparent information for customers. This study aims to design and develop a web-based e-booking application to improve the efficiency of the service booking process at Asri Wedding MUA. The research method applied is Rapid Application Development (RAD), which consists of requirement planning, design workshop, implementation, and testing. Data collection was conducted through direct observation and structured interviews with the business owner. The application was developed using the Laravel 10 framework and MySQL database, and implemented under a client-server web-based architecture.  The implementation results show that the application provides several main features, including user registration and login, service booking, real-time schedule management, proof of payment upload, and an admin dashboard for transaction validation and data management. The Black Box testing results confirm that all core features functioned correctly according to the test scenarios, with valid outcomes in user registration, authentication, booking, payment confirmation, and transaction history. In conclusion, the developed e-booking application successfully digitalizes the manual booking process of Asri Wedding MUA. It enhances operational efficiency and service professionalism while also providing a theoretical implication for the application of RAD in developing web-based information systems for MSMEs. Future work may include integrating automated payment gateways, instant messaging-based reminders, and a Customer Relationship Management (CRM) module to further improve service quality and customer loyalty.